Prevalence and clinical manifestations of male patients with anogenital warts attending a sexually transmitted disease clinic prior HPV vaccine recommendation - Sukhum Jiamton (2018)
© SEAMEO TROPMED Network. All Rights Reserved. Human papillomavirus (HPV) infection is the most common sexually transmitted infection worldwide among men who have sex with men (MSM). A quadrivalent HPV vaccine has been recommended for men in the United States since 2011. We conducted a retrospective study to determine the male anogenital wart burden and patient characteristics at a sexually transmitted disease (STD) clinic to provide baseline data regarding HPV infection. We reviewed the charts of male patients who attended a STD clinic between January 2007 and December 2011 and were diagnosed with having anogenital warts by clinical examination. A total of 181 patients were included in the study. The mean age of patients was 31.1 years, of which 22.7% were MSM and 14.9% had human immunodeficiency virus (HIV) infection. The prevalences of anogenital warts were 22.6% among MSM and 15.1% among HIV infected patients. The prevalence of anogenital warts increased between 2007 and 2011. Compared with patients without anogenital warts at the same STD clinic, patients with anogenital warts were significantly younger and more likely to have multiple sexual partners. Among the HIV infected patients, 63% were MSM; they had a significantly higher anogenital wart recurrence rate. Male anogenital warts posed a significant burden at the STD clinic. A preventive program is needed for anogenital warts, especially among MSM.